The IIMI water balance framework: a model for project level analysis - Perry, C.J. (International Irrigation Management Institute, 1996)
Outlines the IWMI Water Balance Framework, which identifies sources, uses and reuses of water. The framework will be of interest to those involved in the design of irrigation projects and in the formulation of improvements to existing infrastructure of operational rules. Managers of irrigation projects will also find it useful for interpreting water use efficiency, or for identifying interventions to improve the efficiency and sustainability of their projects.